Seasonal variation of sea surface pH and its controls in the Jiaozhou Bay, China. (1st January 2022) - Li, Yunxiao; Yang, Hong; Dang, Jiajia; Yang, Xufeng; Xue, Liang; Zhang, Longjun
Abstract: Coastal waters usually have intense and complicated biogeochemical processes, the interaction of which makes a challenge to identify the dominant factor of pH natural variations such as seasonal signals. In this study, we report seasonal variation and controls of sea surface pH in the highly urbanized Jiaozhou Bay (JZB) based on four cruises conducted in March, July, October 2014 and January 2015. With sea surface temperature increasing, surface pH on the NBS (NIST) scale decreased from 8.16 ± 0.03 in early spring and 8.19 ± 0.02 in winter to 7.96 ± 0.05 in summer and 7.98 ± 0.01 in autumn. The correlation analyses between pH and temperature shows that temperature seems to be a dominant factor of pH seasonal variation. But the mass balance model indicates that biological effect is the most important for the seasonal variation of pH in the JZB. These two apparently different conclusions are due to the fact that the biological effect on pH is greatly weakened (offset by 73%) by the effect of air-sea CO2 exchange. This study highlights the importance of deciphering pH controlling processes in a quantitative manner particularly in shallow and human activities strongly influenced coastal waters, where these processes usually interact each other and readily obscure the dominant factor. Highlights: Seasonal variation in pH covering an annual cycle in the Jiaozhou Bay is shown. Temperature seems to be a dominant factor of pH seasonal variation. Biological effect is the most important indeed, but offset by air-sea exchange. Deciphering pH controlling processes in a quantitative manner is preferred.